SPK Sistem Pendukung Keputusan Promosi Kenaikan Jabatan dengan Fuzzy AHP di STMIK STIKOM Indonesia - Sugiartawan, Putu; Suprihanto, Didit (INFOTEKS (Information Technology, Computer and Sciences), 2020)
Employees who are placed according to their knowledge, skills, and abilities tend to have high motivation, so the resulting performance will also increase. To ensure the right person or employee in the right position too, employee selection has always been a very important part of the company organization, especially in high schools. The decision-making process for promotion of promotion can be completed with a decision support system used by managers as a support for information in solving problems to fill positions, where the performance function can calculate the consideration of each competency possessed by each HR. DSS can provide alternative solutions when a person or group of people is difficult to make the right and appropriate decision. DSS is not to replace the function of decision-makers in making decisions, but only as a tool for decision-makers in carrying out their duties. THE fuzzy AHP method is able to determine the weight with the comparison value of each criterion, and this model Fuzzy-AHP method can cover the limitations of the AHP method, namely imprecision in overcoming Multi-criteria decision making which has subjective criteria. With this method approach, the ranking results of the determination of the position are obtained in accordance with the preferences of the decision-maker